Digitalisasi Ruang Pamer Hasil Karya Mahasiswa pada Program Studi Arsitektur Universitas Malikussaleh - Erna Muliana; Desvina Yulisda (Jurnal Serambi Engineering, 2024)
Architecture is a specialised discipline that emphasises interactive learning processes in studio spaces, resulting in a wide variety of student work. Indeed, some of the most outstanding work from each design studio has the potential to be exhibited to those involved in the world of architecture and to the general public. The importance of exhibiting these works is twofold: firstly, as a form of recognition for the architecture students themselves; and secondly, as a source of inspiration for many parties. In addition, the general public can appreciate the results of the work and gain an insight into the design process that the students go through. However, the architecture building at Universitas Malikussaleh does not have enough space to display student work. This can be attributed to the need for studio space, which is insufficient to accommodate the large number of students and their assignments, as well as the condition of the outside of the building, which hinders the ability to maximise exhibition activities directly on site. This article proposes an alternative digital exhibition space for student work as a solution to the problem of limited space in the architecture programme at Universitas Malikussaleh. It begins with an examination of the alternative media that have been proposed to replace physical spaces, evaluation results, and then goes on to discuss the benefits of digital exhibition spaces for key stakeholders.